Natural convection heat transfer in partially open enclosures containing an internal local heat source - Mariani,V. C. (2007)
A numerical study was conducted to investigate steady heat transfer and flow phenomena of natural convection of air in enclosures, with three aspect ratios (H/W = 1, 2, and 4), within which there is a local heat source on the bottom wall at three different positions, Wh. This heat source occupies 1% of the total volume of the enclosure. The vertical walls in the enclosures are insulated and there is an opening on the right wall. The natural convection is influenced by the difference in temperature between the left and right walls, represented by a Rayleigh number (Ra e), and by local heat source, represented by a Rayleigh number (Ra i). Numerical simulations were performed for several values of the Rayleigh number ranging between 10³ and 10(6), while the intensity of the two effects - the difference in temperature on the vertical walls and the local heat source - was evaluated based on the Ra i/Ra e ratio in the range between 0 and 2500. The analysis proceeds by observing variations in the streamlines and isotherms with respect to the different Ra e, R ratios, aspect ratios, of the radius and positions of the local heat source. The average Nusselt numbers on the hot and cold walls are influenced by different values of the parameters R, Ra e, Wh, and H/W. Results show the presence of different flow patterns in the enclosures studied. Thus, the flow and heat transfer can be controlled by external heating, and local heat source.